A derivate of the antibiotic doxorubicin is a selective inhibitor of dengue and yellow fever virus replication in vitro - Kaptein, Suzanne J (2010)
A doxorubicin derivate, SA-17, that carries a squaric acid amide ester moiety at the carbohydrate (α-l-daunosaminyl) group was identified as a selective inhibitor of in vitro dengue virus (DENV) serotype 2 replication (50% effective concentration [EC(50)] = 0.34 ± 0.20 μg/ml [0.52 ± 0.31 μM]). SA-17 is markedly less cytostatic than the parent compound, resulting in a selectivity index value of ∼100. SA-17 also inhibits yellow fever virus 17D (YFV-17D) replication (EC(50) = 3.1 ± 1.0 μg/ml [4.8 ± 1.5 μM]), although less efficiently than DENV replication, but proved inactive against a variety of enveloped and nonenveloped viruses. SA-17 inhibits in vitro flavivirus replication in a dose-dependent manner, as was assessed by virus yield reduction assays and quantification of viral RNA by means of real-time quantitative reverse transcriptase PCR (RT-qPCR) (∼2 to 3 log reduction). The anti-DENV activity was confirmed using a Renilla luciferase-expressing dengue reporter virus. Time-of-drug-addition studies revealed that SA-17 acts at the very early stages of the viral replication cycle (i.e., virus attachment and/or virus entry). This observation was corroborated by the observation that SA-17, unlike the nucleoside analogue ribavirin, does not inhibit the replication of DENV subgenomic replicons. Preincubation of high-titer stocks of DENV or YFV-17D with ≥5 μg/ml SA-17 resulted in 100% inhibition of viral infectivity (≥3 log reduction). SA-17, however, did not prove virucidal.